Sharia Marketing Strategy in Attracting the Interest of Students of SD Muhammadiyah Satu Sedati, Sidoarjo - Angga Dwi Kurniawan Kusuma; Nurdyansyah Nurdyansyah; Eni Fariyatul Fahyuni (International Consortium of Education and Culture Research Studies, 2020)
The journal entitled